Assessing fair financing of health care in Malaysia / Ng Chiu Wan - Ng, Chiu Wan (2012)
The Malaysian health system has evolved significantly from the public sector dominated delivery system in the 1950’s to a more balanced public private health care system found today. Rapid expansion of the private health sector occurred from the 1990’s and as a consequence, private shares of health financing have been on the increase. This thesis on fair financing of health is motivated by welfare concerns arising from consumption of private health care by the poor, specifically the impact on household welfare caused by household out-of-pocket (OOP) health payments. The concept of fair financing generally holds that society has a moral obligation to ensure that the health needs of the poor can be met without requiring them to fully pay for the health care needed and consumed which they may not otherwise be able to afford. Fair financing for health is examined using data from three comparable nationally representative household expenditure surveys conducted in 1993/94, 1998/99 and 2004/05. The first part of the study, assessment of financial risk protection for health, looks at the distribution of household OOP health payments as well as comparing household OOP payments to two payment thresholds - a catastrophic payment threshold which is set at a predetermined share of household consumption and official Malaysian household poverty lines. In essence this part of the study measures extent to which distributions of OOP payments are favouring richer or poorer persons, levels of catastrophic health payments and medical impoverishment. Availability of data allowed financial risk protection to be assessed for the years 1993, 1998 and 2004. Financial risk protection for health has also been examined by geographical regions in Malaysia (Peninsular, Sabah and Sarawak), urban rural strata and ethnicity. Distributions of OOP payments have also been examined by public private sector providers and categories of health care services. The second part of the study assesses the progressivity of entire health financing system by measuring the progressivity of six health financing sources, namely personal income tax, sales tax, non-tax Federal Government revenues, social security funds from the Employee Provident Fund and Social Security Organisation, private health insurance payments and OOP health payments, singly and in combination. Availability of data and information allowed progressivity to be assessed for the years 1998 and 2004. This study has found evidence of fair financing in Malaysia which included small OOP payment burdens for the average person with distributions favouring richer persons, low levels of catastrophic health payments and medical impoverishment as well as an overall progressive health financing system, mainly made up of four progressive financing sources namely personal income tax, social security funds, OOP health payments and private health insurance payments. As expected, this study has found that OOP payments have been predominantly for the purchase of private health care, mainly for non-hospital based care and pharmaceuticals. Financial risk protection was higher among some sub-populations in the country including those living in Sarawak, rural areas and the Chinese. However, over time from 1993 to 2004, some features of fair financing appeared to have diminished where the distribution of OOP payments and households incurring catastrophic health payments became less concentrated among the rich. The overall health financing system was found to be progressive in 1998 and 2004. Changes in progressivity were too small to make a definite conclusion of the trends over time. Declining fairness in health financing in Malaysia may be explained by increasing OOP payments for private care and increasing uptake of private health insurance by poorer households. This in turn may be due in part to declining quality of care provided by the public health system which may have been partially caused by the rapidly expanding private health sector. If so, the situation is likely to worsen further if remedial actions are not taken. This study has provided two main health policy lessons with regards to private provision and private financing of health care. The first is that extensive taxation-based funding of health care can ensure fair financing despite high OOP health payment shares of total health financing in a country. The second is that a situation of fair financing can co-exist with a large private health sector financed mainly from OOP payments. The main message is that it is not so much the quantum of payments that matters but rather the distribution of payments.